Ergonomic Risk Evaluation of Manual Material Handling in Brick Production - Indah Pratiwi; Valeska Salsabil Kalyana (Jurnal Ilmiah Teknik Industri, 2022)
The manual material handling (MMH) activity of making bricks causes workers to use energy throughout their body to do work so that it can pose a potential ergonomic hazard. Ergonomics hazards caused are fatigue in the muscles due to repetitive movements, poor work posture, too heavy load, inadequate tools, unsupportive environmental conditions. Complaints of Musculoskeletal disorders (MSDs) that accumulate will have a major impact on bone structure disorders and muscle disorders.The purpose of this study was to evaluate the ergonomic risks and complaints of MSDs in MMH activities using a trolley. The research method used is the risk assessment of pushing and pulling (RAPP) tool and Nordic body map (NBM). The RAPP Tool consists of 9 assessments with a rating scale of good, reasonable, poor and unacceptable. Furthermore, using the NBM which mapped 28 body parts with a rating scale of no pain, moderately ill, sick and very sick.The results of the study contained 3 assessments of the RAPP Tool with the highest score, including floor surface, posture, and condition of the tool. The results of the NBM found that the body parts that often felt complaints were the back, waist, buttocks, left knee, right knee, left leg and right leg. The conclusion is that workers with high RAPP scores have an impact on high levels of muscle complaints so that improvements need to be made immediately to reduce ergonomic risks to workers.